A reliable screening of mycotoxins and pesticide residues in paprika using ultra-high performance liquid chromatography coupled to high resolution Orbitrap mass spectrometry. (February 2016) - Reinholds, Ingars; Pugajeva, Iveta; Bartkevics, Vadims
Abstract: In this study, an ultra-high performance liquid chromatography (UHPLC) coupled to a high resolution Orbitrap mass spectrometry (Orbitrap-HRMS) was demonstrated as a promising technique in high-throughput method development for the routine analysis and contamination control of mycotoxins and pesticide residues in spices. The method was applied for the analysis of fifty ground paprika samples containing blends of sweet and hot paprika harvested in Brazil and China. The efficiency and detection sensitivity of the used UHPLC-Orbitrap-HRMS technique were compared to the results obtained using a triple quadrupole tandem mass spectrometric detector (UHPLC-QqQ-MS/MS). The values of recovery (75–120%) and repeatability (8–15%) for both methods, calculated as the average (n = 5) from the results of spiked (10–500 μg kg −1 ), paprika samples, were in good conformity to the relevant EU guidelines. The high resolution of the used Orbitrap-HRMS technique provided a better sensitivity for quantitative determination of several pesticide contaminants in paprika, compared to the results obtained by the QqQ-MS/MS method and were comparable in case of mycotoxins. The results of analysis demonstrated the ubiquitous presence of three mycotoxins (fumonisin B1, ochratoxin A, and sterigmatocystin) and twelve pesticide residues in paprika. The concentrations of determined contaminants were below the MRLs set by the Regulations of the European Union with exception of iprovalicarb, which violated the EU MRL in two samples of hot paprika. In addition, a notable difference in the concentration of fumonisin B1 was determined depending on the harvest period (2009–2013), reaching the maximum concentrations of 33 μg kg −1 in sweet paprika and 140 μg kg −1 in hot paprika. There was no significant correlation found between the determined mycotoxin contamination levels and the pesticide residues, with the sole exception of decreased fumonisin B1 content in samples with an elevated concentration of metalaxyl fungicide. Highlights: An Orbitrap based method for simultaneous analysis of contaminants in paprika was developed. The results obtained by the Orbitrap-MS and QqQ-MS/MS showed a good correlation. Fumonisin B1 was detected in 11% of sweet paprika and 71% of hot paprika samples. The presence of eleven pesticides below the MRLs was detected. The content of iprovalicarb exceeded the MRL in two samples of hot paprika.